The Relationship between the Jhungrojhung Tradition in Kajjan Village and the Hadith of Make an Easy on Others: Hubungan antara Tradisi Jhungrojhung di Desa Kajjan dengan Hadits Meringankan Beban Orang Lain - Abdul Hakim, Al Hasan; Fathur Rozi; Mustofa; Holil; Moh. As’ad (Jurnal Living Hadis, 2023)
Mutual cooperation, which are a characteristic of Indonesian society have experienced many shifts because the motive is no longer caring for the surrounding community, but the money that is the reward. However, there are still forms of cooperation practices based on caring, such as those in Kajjan Village which is called Jhungrojhung. This article discusses the relationship between the practice of jhungrojhung and the hadith of the Prophet as its main basis. Furthermore, this research focuses on two problem formulations; First, what is the essence of the Jhungrojhung tradition in Kajjan Village, District. Blega Kab. Bangkalan?; and second, how does the Jhungrojhung Tradition correlate with the hadith of the Prophet saw? These questions were analyzed using a qualitative approach based on field studies and supported by a phenomenological approach. As a result, there was no shift in values ​​in the practice of Jhungrojhung in Kajjan village because there was no economic class dichotomy in the Kajjan village community. Apart from that, the Prophet's hadith regarding for people who assist others is the main motivation and practical basis for this practice, so its existence can still be felt today.